Analyzing Qualitative Data with MAXQDA Text, Audio, and Video - Kuckartz, Udo.; Rädiker, Stefan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents strategies for analyzing qualitative and mixed methods data with MAXQDA software, and provides guidance on implementing a variety of research methods and approaches, e.g. grounded theory, discourse analysis and qualitative content analysis, using the software. In addition, it explains specific topics, such as transcription, building a coding frame, visualization, analysis of videos, concept maps, group comparisons and the creation of literature reviews. The book is intended for masters and PhD students as well as researchers and practitioners dealing with qualitative data in various disciplines, including the educational and social sciences, psychology, public health, business or economics.
Introduction: Analyzing Qualitative Data with Software -- Getting to Know the Interface of MAXQDA -- Setting up a Project and Importing Data -- Transcribing Audio and Video Recordings -- Exploring the Data -- Coding Text and PDF Files -- Coding Video Data, Audio Data, and Images -- Building a Coding Frame -- Working with Coded Segments and Memos -- Adding Variables and Quantifying Codes -- Working with Paraphrases and Summaries, Creating Case Overviews -- Comparing Cases and Groups, Discovering Interrelations and Using Visualizations -- Analyzing Mixed Methods Data -- Working with Bibliographic Information and Creating Literature Reviews -- Analyzing Focus Group Data -- Analyzing (Online) Survey Data with Closed and Open-Ended Questions -- MAXMaps: Creating Infographics and Concept Maps -- Collaborating in Teams -- Analyzing Intercoder Agreement -- Documenting and Archiving the Research Process.
Keywords: Sociology -- Methodology; Social sciences -- Statistical methods; Education -- Research; Mathematical statistics -- Data processing; Biometry; Statistics .; Sociological Methods; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy; Research Methods in Education; Statistics and Computing; Biostatistics; Statistics in Business, Management, Economics, Finance, Insurance